Torque ripple attenuation of PMSM using improved robust two-degree-of-freedom controller via extended sliding mode parameter observer. (October 2022) - Huang, Mingfei; Deng, Yongting; Li, Hongwen; Wang, Jianli
Abstract: Torque ripple caused by flux harmonics, nonlinearity of inverter and current measurements decreases the accuracy of the servo control system, which limits the application of permanent magnet synchronous motor (PMSM) with high precision requirement. To reduce torque ripple, this paper proposes an improved robust two-degree-of-freedom controller (IR-2DOFC) based on an extended sliding-mode parameter observer (ESMPO) for a PMSM. The IR-2DOFC is constructed around the 2DOFC with iterative learning control (ILC) and a series-connecting structure, which not only suppresses unmodeled disturbances and periodic components, but also attenuates the negative impact of ILC on the dynamic response. Meanwhile, to improve the robust stability of the IR-2DOFC, ESMPO identifies the mechanical parameters so that they can be employed to further establish the IR-2DOFC parameters. Additionally, the observed disturbances can be regarded as a feed-forward compensation component to the IR-2DOFC, which enhances the disturbance-rejection performance. Simulations and experiments show that the IR-2DOFC with ESMPO has an improved dynamic response performance, which exhibits better robustness with respect to internal and external load disturbances and harmonics torque compared with proportional–integral (PI) and PI-ILC controllers. Highlights: This paper proposes a control strategy by combining the robust two degree of freedom controller (IR-2DOFC) and extended sliding mode parameter observer (ESMPO). The IR-2DOFC is utilized to suppress the unmodeled disturbances and periodic components. The ESMPO is designed to estimate the external disturbances and add a feedback compensation item to the output of the IR-2DOFC.